The Lancet One Health Commission: harnessing our interconnectedness for equitable, sustainable, and healthy socioecological systems - Winkler, A.S.; Brux, C.M.; Carabin, H.; Neves, C.G. das; Häsler, B.; Zinsstag, J.; Fèvre, Eric M.; Okello, A.; Laing, G.; Harrison, W.E.; Pöntinen, A.K.; Huber, A.; et al. (Elsevier, 2025)
Industrialisation, urbanisation, and globalisation have substantially improved human life expectancy over the past century. In tandem, an expanding array of interlinked threats to humans, other animals, plants, and a myriad of other biotic and abiotic elements in our shared ecosystems has been generated. These threats include emerging and re-emerging infectious diseases, antimicrobial resistance (AMR), non-communicable diseases (NCDs), jeopardised food safety and security, freshwater scarcity, climate change, pollution, and biodiversity loss. These pressing health and sustainability challenges exceed the scope of any single discipline, government ministry, or societal sector, underscoring the need for interdisciplinary, transdisciplinary, and multisectoral collaboration, as well as for a socioecologically oriented systems perspective that appreciates the fundamental interconnections between humans, other animals, and the wider ecosystem.